HOOK WORM INFESTATION IN TEN WEEKS OLD INFANT - Wazir, Mehr Dil; Shah, S. Humayun; Muhammad, Wali (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: Hook worm infestation is very rare in early age. We report a 2Vt months old infant who presented with severe anaemia and passage of dark colour stools. There was no history of bleeding and no signs of haemolysis were noticed. Stool examination revealed ova of Ankylostoma duodenale. Stool examination of the mother also revealed hook worm infestation. As 6-8 weeks are needed to pass ova in the stools from the date of penetration of the skin by the larvae, the possible cause in this was infection through the skin in the 1st few days after delivery or as a result of laying down the child on infected ground.